IMPLEMENTATION OF NUTRITION-SENSITIVE INTERVENTIONS POLICY FOR STUNTING DECREASE IN BLORA REGENCY - Nadia Feryka Probohastuti; Aloysius Rengga (Journal of Public Policy and Management Review, 2019)
The stunting rate in Blora Regency is one of the relatively high because it has passed the maximum limit set by WHO, which is 20%, therefore several efforts have been made to overcome this problem by implementing a nutrition-sensitive interventions policy to decreased stunting. The purpose of this research is to describe how the implementation of nutrition-sensitive interventions policy for decreasing stunting in Blora Regency and to identify inhibiting factors of the policy implementation. This research uses a qualitative method with a descriptive approach. The results showed that not all of the implementation of the nutrition-sensitive interventions decreased stunting in Blora Regency has run optimally. It can be seen from programs that include, 1) increasing drinking water supply and sanitation; 2) increasing access and quality of nutrition and health services; 3) increasing awareness, commitment, parenting practices, and nutrition for mothers and children; 4) increasing access to nutritious food. In every effort to increase, there are programs that have not been able to have a maximium impacton reducing stunting. This is because there are a lack of human resources and budgets, the dissemination of information has not maximized, lack of society support and awareness, as well as invalid data. Suggestions that can be given are allocation of village funds for community nutrition development, strengthening the role of cadres in disseminating information and public nutrition detection, and providing marriage preparation courses by providing related to household life, especially health and nutrition issues so one day they will not give birth to stunting children.